ANALISIS PERPANJANGAN MASA JABATAN KEPALA DESA DI TINJAU DARI PERSPEKTIF POLITIK HUKUM - NIM. A1011211058, LUHER (Jurnal Fatwa Hukum, 2025)
Abstract This research examines the Analysis of Extension of Term of Office of Village Heads Reviewed from the Perspective of Legal Politics. The main focus of the problem in this study is How the Legal Politics Determine the Term of Office of Village Heads in the History of Legislation in Indonesia. The purpose of this study is to analyze the Legal Politics of Determining the Term of Office of Village Heads in the History of Legislation in Indonesia and to analyze the Ideal Term of Office of Village Heads to ensure the effectiveness and sustainability of leadership at the village level. This study uses a normative legal research methodology whose research nature uses a descriptive analysis approach. Data were obtained through literature studies, legislative approaches and analysis of related legal documents. The results of the study show that the regulation of the term of office of the village head has undergone various changes, starting from Law Number 5 of 1979 concerning Village Government by setting the term of office of the village head at 8 years and can be re-elected for 1 term, Law Number 22 of 1999 concerning Regional Government which changes the term of office of the village head to 10 years in 1 period and can be re-elected once, Law Number 32 of 2004 concerning Regional Government returns the term of office of the village head to 6 years and can serve a maximum of 2 terms, Law Number 6 of 2014 concerning Villages sets the term of office of the village head to 6 years with a maximum of 3 consecutive or non-consecutive terms, to Law Number 3 of 2024 concerning Villages sets the term of office of the village head to 8 years with a maximum of 2 terms. These changes reflect the dynamics of village government needs, political stability and regional goals, with the expected achievement being the creation of a democratic, stable village government that is able to improve community welfare. Keywords: Legal politics; Term of office; Village head."ƒ Abstrak Penelitian ini mengkaji tentang Analisis Perpanjangan Masa Jabatan Kepala Desa Ditinjau dari Perspektif Politik Hukum. Fokus permasalahan utama dalam penelitian ini yaitu Bagaimana Politik Hukum Penentuan Masa Jabatan Kepala Desa dalam Sejarah Peraturan Perundang-undangan di Indonesia. Adapun tujuan dari penelitian ini yaitu untuk menganalisis Politik Hukum Penentuan Masa Jabatan Kepala Desa dalam Sejarah Peraturan Perundang-undangan di Indonesia dan menganalisis Masa Jabatan Ideal Kepala Desa untuk memastikan efektivitas dan keberlanjutan kepemimpinan di tingkat desa. Penelitian ini menggunakan metodologi penelitian hukum normatif yang sifat penelitiannya menggunakan pendekatan deskriptif analisis. Data diperoleh melalui studi kepustakaan, pendekatan perundang-undangan dan analisis dokumen hukum terkait. Hasil penelitian menunjukan bahwa pengaturan masa jabatan kepala desa telah mengalami berbagai perubahan, mulai dari Undang-Undang Nomor 5 Tahun 1979 tentang Pemerintahan Desa dengan menetapkan masa jabatan kepala desa 8 tahun dan dapat dipilih kembali 1 kali masa jabatan, Undang-Undang Nomor 22 Tahun 1999 tentang Pemerintahan Daerah yang mengubah masa jabatan kepala desa menjadi 10 tahun dalam 1 periode dan dapat dipilih kembali 1 kali masa jabatan, Undang-Undang Nomor 32 Tahun 2004 tentang Pemerintahan Daerah mengembalikan masa jabatan kepala desa menjadi 6 tahun dan dapat menjabat maksimal 2 periode, Undang-Undang Nomor 6 Tahun 2014 tentang Desa menetapkan masa jabatan kepala desa menjadi 6 tahun dengan maksimal 3 kali masa jabatan berturut-turut atau tidak berturut-turut, hingga Undang-Undang Nomor 3 Tahun 2024 tentang Desa menetapkan masa jabatan kepala desa menjadi 8 tahun dengan maksimal 2 periode. Perubahan tersebut mencerminkan dinamika kebutuhan pemerintahan desa, stabilitas politik dan tujuan daerah, dengan capaian yang diharapkan adalah terciptanya pemerintahan desa yang demokratis, stabil dan mampu meningkatkan kesejahteraan masyarakat. Kata kunci: Politik hukum; Masa jabatan; Kepala desa.